Increasing the Soil Resistance Value in the 20 kV Medium Voltage Distribution Network using the Soil Treatment method - Taryo, Taryo; Fauzi, Andri Ahmad; Rosidi, Rosidi (PROtek : Jurnal Ilmiah Teknik Elektro, 2025)
This study aims to enhance soil resistivity in a 20 kV electrical distribution network using a mixture of rice husk ash and mangrove wood charcoal. Rice husk ash is an additive known to reduce grounding resistance due to its water-absorbing properties, maintaining soil moisture. Effective grounding system is crucial to ensure fault currents can safely dissipate into the ground, protecting equipment and maintaining electrical distribution continuity. PUIL 2000 standards mandate soil resistivity below 5 Ω. The study method involved initial soil resistivity measurements using a Digital Earth Tester 4015 A, adding various mixtures of rice husk ash and mangrove wood charcoal around electrode planting areas, and periodic resistivity measurements over five days after four mixture additions. Scheme 1, 70% mangrove wood charcoal and 30% rice husk ash. Scheme 2, 30% mangrove wood charcoal and 70% rice husk ash. Scheme 3, 100% rice husk ash. Scheme 4, 100% mangrove wood charcoal. Results showed significant resistivity reduction, with the 30% rice husk ash and 70% mangrove wood charcoal mixture lowering resistivity to an average of 3.78 Ω, reflecting a 43.5% decrease from the initial value. Adding rice husk ash and mangrove wood charcoal to field soil enhanced soil conductivity, enabling resistance reduction to meet safety standards. This study recommends this blend as an effective and economical alternative to reduce grounding resistance in 20 kV electrical distribution systems.